FACTORS INFLUENCING CIVIC AND POLITICAL ENGAGEMENT AMONG STUDENTS IN KAZAKHSTAN - Rakhimov, Bakhtiyar; Bolatuly, Ratmir; Igenbekova, Zhanna (Nazarbayev University, Graduate School of Public Policy, 2021)
Participation of the young generation in democracy promotes active citizenship, strengthens social responsibility and can enhance democratic processes and institutions. Young people can offer to societies much, from innovation to creativity and new thinking, therefore young people today will become leaders and decision-makers in the future. The research covers both undergraduate and graduate students since they are young people attending higher education institutions. In order to collect information for the research literature review was studied, a survey distributed among students in 6 universities via online service and online interviews conducted with representatives of 5 universities who are responsible for student affairs. Based on survey and interview results conducted, our research team learned that certain factors significantly affect the level of civic and political engagement of students. The majority of the hypotheses were not confirmed and survey analysis demonstrated unpredicted results. We identified that there are several factors influencing the civic and political engagement of students that showed some issues to be improved. Therefore, the main recommendations are to conduct youth policy more, conduct transparent dialogues between executive bodies and youth, develop mass media content for youth, increase the number of youth organizations, and do more research on this topic.
Keywords: Type of access: Open Access; civic engagement; political engagement; citizenship